SOLVING PRODUCTION BOTTLENECK THROUGH TIME STUDY ANALYSIS AND QUALITY TOOLS INTEGRATION - Abdul Azid, Ishak; Che Ani, Mohd Norzaimi; Abdul Hamid, Siti Aisyah; Kamarudin, Shahrul (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
In this paper, a process improvement model that is enhanced through the integration of motion time study and quality tools is proposed. The model is intended to support the process improvement drive particularly for practitioners of time and motion study approach. Generally, when using the motion time study approach, there is a limitation in terms of identifying the optimal solutions once all the relevant data had been gathered and analyzed. Therefore, by integrating two approaches; the classification and the amount of time required to perform a task is determined through motion time study, and the quality tools by means of Modified Pareto chart, Ishikawa diagram and Failure Mode and Effect Analysis (FMEA); the root causes of the bottleneck problem in production are identified and analyzed. It is then further expanded by adopting a brainstorming approach to identify the optimal solution. The developed integration model is validated through a case study. The results obtained from the case study shows that the production output has significantly improved by 10 percent through the reduction in time and processes in completing the assembly work. This has also resulted in improvement in product quality and reduction in the operation costs.